المسؤولية الاجتماعية لمؤسسات تجاه العاملين في ظل معيار المساءلة الاجتماعية 8000 -دراسة استقصائية بمؤسسة نفطال- وحدة قسنطينة - سايح الطيب (جامعة الوادي University Of Eloued, 2024)
The study aims to reveal the reality of corporate social responsibility practices towards employees in the naftal company -Constantine unit, according to the requirements defined in SA8000. To this end, a questionnaire to measure the variables of the study was developed. the study population is composed of all employees of the company, and our choice fell on a convenience sample of 50 respondents, spread over well-defined departments .The results of the research conducted show that that the application of the requirements contained in SA8000 has not yet reached the stage of maturity. And in response of these findings, the research had made suggestions to enable the company to achieve a better commitment to responsible practices towards employees
Corporate Social Responsibilitytowards employees as claimed by SA8000 An exploratory study at naftal company- Constantine unit
Keywords: الميؤولية الاجتماعية للمؤسسات; العمال; Corporate Social Responsibility; Workers; SA8000